2014
DOI: 10.1371/journal.pntd.0002999
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Miltefosine Susceptibility of a Leishmania amazonensis Isolate from a Patient with Diffuse Cutaneous Leishmaniasis

Abstract: Miltefosine was the first oral compound approved for visceral leishmaniasis chemotherapy, and its efficacy against Leishmania donovani has been well documented. Leishmania amazonensis is the second most prevalent species causing cutaneous leishmaniasis and the main etiological agent of diffuse cutaneous leishmaniasis in Brazil. Driven by the necessity of finding alternative therapeutic strategies for a chronic diffuse cutaneous leishmaniasis patient, we evaluated the susceptibility to miltefosine of the Leishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
2
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 38 publications
(49 reference statements)
4
54
2
8
Order By: Relevance
“…In addition, these results show that sensitivity of parasites to miltefosine in the RAW264.7 macrophage cell line was comparable with sensitivity in primary macrophages. The observations above are in agreement with several published studies that have reported that Leishmania species (and isolates) exhibit differences in sensitivity to miltefosine and that intracellular parasites are more sensitive than extracellular parasites to miltefosine (Coelho, Trinconi, Costa, & Uliana, 2014;Seifert et al, 2010). On the basis of those observations, we hypothesised that the increased efficacy of miltefosine on intracellular parasites is mediated by its effects on a host target of the drug.…”
Section: Miltefosine Has Direct Effects On Leishmania Parasitessupporting
confidence: 92%
“…In addition, these results show that sensitivity of parasites to miltefosine in the RAW264.7 macrophage cell line was comparable with sensitivity in primary macrophages. The observations above are in agreement with several published studies that have reported that Leishmania species (and isolates) exhibit differences in sensitivity to miltefosine and that intracellular parasites are more sensitive than extracellular parasites to miltefosine (Coelho, Trinconi, Costa, & Uliana, 2014;Seifert et al, 2010). On the basis of those observations, we hypothesised that the increased efficacy of miltefosine on intracellular parasites is mediated by its effects on a host target of the drug.…”
Section: Miltefosine Has Direct Effects On Leishmania Parasitessupporting
confidence: 92%
“…major [52] or L . amazonensis [53] with mutations in the MT did not show reduced infectivity, and the potential for resistance to multiple drugs by a single point mutation remains real.…”
Section: Discussionmentioning
confidence: 99%
“…APCs not only demonstrate cytotoxic effects against various types of malignant cells but are also highly effective against parasites such as Leishmania spp. [1,[6][7][8][9][10], African Trypanosoma spp. [11], Entamoeba histolytica [12], Acanthamoeba spp., Schistosoma mansoni [13], Plasmodium falciparum [14], Gram-positive pathogenic bacteria [15,16], pathogenic fungi [17,18] and RNA or DNA viruses [19].…”
Section: Introductionmentioning
confidence: 99%